Feeding and housing management practices of dairy animals in Rajnandgaon of Chhatisgarh plain - DEORAS, RAJIV; NEMA, R K; TIWARI, S P; SINGH, MOHAN (The Indian Journal of Animal Sciences, 2014)
Data were collected from 300 farmers from rural area covering 20 villages of all 9 blocks and 100 farmers from Rajnandgaon city to study. The information was collected from respondents on feeding and housing management practices of dairy animals by a questionnaire prepared. In urban area significantly (P<0.01) higher (26%) number of farmer provide green fodders throughout the year in comparison to rural farmers(2.33%). Maiority of the farmers (99.66%) did not prefer chaffing of fodder in rural areas, whereas, in urban area only 6% preferred it. Almost all farmers of rural (100%) and urban area (93%) sent their animals out for grazing. Farmers in rural(73%) and urban(67%) area fed their livestock with crop residues like paddy straw, wheat straw and lakhdin (Lathyrus) straw. In rural area (96%) farmers fed their livestock with only brans and chunnies as a substitute of concentrate mixture. However, 4% farmers provided their animals with balanced feed. In urban area significantly (P<0.01) higher number of farmers provided balanced cattle feed to their animals, and 100% farmers purchased it from local market. Significantly higher number (97.33%) of farmers of rural area provided common salt to their animals in comparison to 27% urban farmers. Significantly (P<0.01) higher number of farmer provided mineral mixture in urban area as compared to no farmer in rural area. The housing managemental practices adopted in majority of cases were unhygienic, unhealthy and not according to the recommendation in rural areas as compared to urban area. There is need to provide knowledge of scientific feeding and housing management practices to the farmers through extension education programme.